Listening Attitude as a Foundation for Communication and Democracy in the Classroom - Motta Ávila, J. Humberto (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article seeks to illustrate the listening attitude of students and teachers as a foundation for communication and democracy in the classroom. It presents a synthesis of the current diagnosis on classroom listening, as well as the theoretical referents that support the listening-communication-democracy relation presented in this study. The methodological process is based on the traditions of phenomenology and reflexive hermeneutics. As a result, the act of listening is developed an essential condition for classroom pedagogy. This implies the need to keep listening attitudes away from dissonance and degradation, understanding its importance for a democratic approach to conversation.